Language and the Study of Africa - (:unkn) unknown (My University, 2013)
This is an annotated introductory bibliography for African languages and linguistics, attempting to give at least some information on each family, as well as on more general questions of phonology, morphology, syntax, and orthography.
Keywords: African Research